Effects of in vitro supplementation with Syzygium cumini (L.) on platelets from subjects affected by diabetes mellitus. (17th November 2015) - Raffaelli, Francesca; Borroni, Francesca; Alidori, Alessandro; Tirabassi, Giacomo; Faloia, Emanuela; Rabini, Rosa Anna; Giulietti, Alessia; Mazzanti, Laura; Nanetti, Laura; Vignini, Arianna
Abstract: The aim of this study was to assess the in vitro effects of Syzygium cumini (L.) (Sc) incubation on platelets from patients with diabetes, in order to test its efficacy as a potential adjuvant therapy. This study was performed on 77 patients with diabetes [29 in good (DMgc ) and 48 in poor glycemic control (DMpc )] and 85 controls. In patients, platelets were analyzed at recruitment and after in vitro Sc incubation (final concentration of 200 µg/ml for 3 hours at 37 °C), whereas in controls only basal evaluation was performed. Lipoperoxide and nitric oxide (NO) levels, superoxide dismutase (SOD) and Na + /K + ATPase activities, total antioxidant capacity (TAC), and membrane fluidity tested by anisotropy of fluorescent probes 1 -(4-trimethylaminophenyl)-6-phenyl-1, 3, 5-hexatriene (TMA-DPH) and 1-6-phenyl-1, 3, 5-hexatriene (DPH) were determined. Collagen-induced platelet aggregation was also evaluated. In vitro Sc activity counteracts oxidative damage, by improving platelet function through augmented membrane fluidity and Na + /K + ATPase activity; it also enhances antioxidant system functionality by increasing NO levels, SOD activity, and TAC and by decreasing lipoperoxide levels both in whole samples and in DMgc and DMpc . In addition, a slight tendency towards collagen-induced platelet aggregation decrease after Sc was observed. However, all these parameters, even after improvement, did not reach the levels of control subjects. Our results suggest that Sc may have a preventive and protective effect in oxidative damage progression associated with diabetes mellitus and its complications. If our data will be confirmed, Sc supplementation might become a further tool in the management of this disease, especially in view of its easy availability, safety, low cost, and absence of side effects.